Various Corneal Foreign Body Materials - Fitriani, Dila Nur; Nurwasis (Universitas Airlangga, 2024)
Introduction: Cornea is an important refractive part of the eye. The corneal foreign body can disturb corneal function, depending on its material. Any materials are inert and can be retained with serial observation, while others can cause an inflammatory reaction. Purpose: To determine the effects of various foreign body materials on the cornea. Review: Corneal foreign body materials are divided into non-organic and organic materials. Organic foreign bodies (plant and insect parts) often cause severe inflammation; meanwhile, the effects of non-organic foreign bodies (metal, glass, graphite) depend on their materials. Some metals, such as iron and copper, can develop a stained deposition, disturb corneal clarity, and lead to inflammation. Other metals such as gold, silver, and platinum are almost inert and cause little or no reaction. Glass, sand, or stone is relatively inert if it is sterile. Intrastromal graphite is also inert, however, organic materials are associated with infection. Wood can lead to bacterial or fungal infection. Insect parts such as caterpillar hair can cause ophthalmia nodosa, and insect stings elicit an inflammatory response. Conclusions: Any non-organic corneal foreign bodies (gold, silver, platinum, glass, sand, stone, and graphite) may be retained safely if the removal of the foreign body results in significant scarring, which can distort the topography of the cornea. Iron, copper, and organic materials (wood and insect parts) must be removed due to their toxicity or risk of infection.